The PRELIMINARY RESEARCH OF DDD-E MODEL: A FRAMEWORK FOR DEVELOPING WEBSITE INFOGRAPHIC FOR ISLAMIC EDUCATION LITERACY - Afi Rizqiyah,; Muhammad Thohir,; Amir Mu’tashim Billah,; Ali Uroidli, (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2024)
Literacy is inextricably linked to successful learning outcomes. Research consistently demonstrates that students' literacy challenges encompass difficulties in comprehending specific types of learning materials. Infographics, characterized by their visual appeal, clarity, and concise presentation, have the potential to serve as an effective medium for facilitating students' understanding of educational content. The present study investigates the decision-making and design processes involved in developing website-based infographics as a tool for enhancing Islamic Education literacy. Framed within the initial stages of Research and Development (R&D), data collection encompassed interviews, observations, document analysis, and a comprehensive review of relevant literature. The subsequent qualitative analysis involved data reduction, presentation, and the formulation of conclusions. Findings indicated that the selection of media for development was predicated upon a thorough consideration of learning objectives, the scope of the media, prerequisite skills, and available resources. The design stage comprised a series of activities aimed at creating engaging and informative website infographics. These infographics are theoretically posited to capture students' attention, facilitate memory retention, and foster a deeper comprehension of the subject matter. It is anticipated that this research will serve as a valuable reference for the development of website infographics as literacy tools, employing systematic procedures and sound pedagogical assumptions. Abstrak: Literasi memiliki keterkaitan yang kuat dengan keberhasilan proses pembelajaran. Temuan di lapangan mengindikasikan adanya permasalahan literasi pada siswa, termasuk kesulitan dalam memahami jenis materi pembelajaran tertentu. Infografis, dengan karakteristiknya yang menarik, jelas, dan mudah dipahami, dapat menjadi media yang efektif dalam memfasilitasi pemahaman siswa terhadap materi pembelajaran. Penelitian ini bertujuan untuk menganalisis tahap penentuan (decide) dan perancangan (design) infografis berbasis website sebagai media literasi dalam pembelajaran Pendidikan Agama Islam (PAI). Penelitian ini merupakan bagian awal dari Research and Development (R&D). Pengumpulan data dilakukan melalui wawancara, observasi, dokumentasi, dan studi literatur, kemudian dianalisis secara kualitatif meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa penentuan media yang akan dikembangkan mempertimbangkan tujuan pembelajaran, cakupan media, kemampuan prasyarat siswa, dan sumber daya yang tersedia. Tahap perancangan meliputi serangkaian kegiatan untuk merancang infografis berbasis website. Secara teoritis, infografis website yang dikembangkan diharapkan mampu menarik perhatian siswa, serta memudahkan siswa dalam mengingat dan memahami materi ajar. Penelitian ini diharapkan dapat menjadi acuan dalam pengembangan infografis website sebagai media literasi yang efektif, dengan prosedur yang sistematis dan asumsi yang logis.